The Impact Of Implementing Investigation Audit On Fraud: A Literature Study - Zumratul Meini; Khairul Saleh L. Tobing; Syamsudin; Kumba Digdowiseiso; Siti Nurain Muhmad (CV ODIS, 2023)
Increasing cases of fraud in today's complex and global business environment. The implementation of investigative audits for fraud has a significant impact on the context of a company's finances and reputation. The aim of this research is to evaluate how investigative audits influence fraud detection, prevention and handling. The method used is a literature review of related research and case studies in various industrial sectors. The results of this research show that the effective implementation of investigative audits can identify fraudulent acts early, prevent abuse, and reduce the risk of financial loss. Investigative audits can also strengthen stakeholder trust, enhance reputation, and create the atmosphere of transparency necessary to maintain positive relationships with customers and business partners. The research results show that investigative audits are not only an important step in reducing financial losses due to fraud but also have a positive impact on the company's image and reputation. Therefore, organizations should consider implementing investigative audits as an integral part of their risk management strategy, which in turn can contribute to long-term sustainability and success